Higher prevalence of harbouring BCR::ABL1 in first-degree relatives of chronic myeloid leukaemia (CML) patients compared to normal population - Kuan, Jew Win; Anselm Su, Ting; Sim, Sai Peng; Tay, Siow Phing (BioMed Central Ltd, 2024)
BACKGROUND: The role of familial influence in chronic myeloid leukaemia (CML) occurrence is less defined. Previously, we conducted a study to determine the prevalence of harbouring BCR::ABL1 in our local adult normal population (designated as Study(N)). We present our current study, which investigated the prevalence of harbouring BCR::ABL1 in the normal first-degree relatives of local CML patients (designated as Study(R)). We compared and discussed the prevalence of Study(R) and Study(N) to assess the familial influence in CML occurrence. METHODS: Study(R) was a cross-sectional study using convenience sampling, recruiting first-degree relatives of local CML patients aged >/= 18 years old without a history of haematological tumour. Real-time quantitative polymerase chain reaction standardised at the International Scale (BCR::ABL1-qPCR(IS)) was performed according to standard laboratory practice and the manufacturer's protocol. RESULTS: A total of 96 first-degree relatives from 41 families, with a mean age of 39 and a male-to-female ratio of 0.88, were enrolled and analysed. The median number of relatives per family was 2 (range 1 to 5). Among them, 18 (19%) were parents, 39 (41%) were siblings, and 39 (41%) were offspring of the CML patients. Study(R) revealed that the prevalence of harbouring BCR::ABL1 in the first-degree relatives was 4% (4/96), which was higher than the prevalence in the local normal population from Study(N), 0.5% (1/190). All four positive relatives were Chinese, with three of them being female (p > 0.05). Their mean age was 39, compared to 45 in Study(N). The BCR::ABL1-qPCR(IS) levels ranged between 0.0017%(IS) and 0.0071%(IS), similar to Study(N) (0.0023%(IS) to 0.0032%(IS)) and another study (0.006%(IS) to 0.016%(IS)). CONCLUSION: Our study showed that the prevalence of harbouring BCR::ABL1 in the first-degree relatives of known CML patients was higher than the prevalence observed in the normal population. This suggests that familial influence in CML occurrence might exist but could be surpassed by other more dominant influences, such as genetic dilutional effects and protective genetic factors. The gender and ethnic association were inconsistent with CML epidemiology, suggestive of a higher familial influence in female and Chinese. Further investigation into this topic is warranted, ideally through larger studies with longer follow-up periods.